Early Infant Feeding and Body Composition In Pre-School Children - Anderson, Alex K.; Whitworth, Christina; Tandoh, Marina A. (International Journal of Pediatrics and Child Health, 2016)
Objective: The purpose of this study was to examine the association between early infant feeding and childhood adiposity. Method: This was a cross-sectional study of 29 pre-school age (4 to 6 years) children and their mothers. Mothers were interviewed using a structured questionnaire to assess early infant feeding practices, while the children’s body composition was measured using the BOD POD Pediatric Option Body Composition System. Results: The mean age of the children was 4.9 ± 0.8 years, 82.8% Caucasian and 17.2% Black/African American, while 65.5% were female. None of the mothers reported alcohol consumption or smoking during the pregnancy with the child. Of the 29 children in the study, 41.4% were exclusively breastfed for at least 3 months, 48.3% mix-fed and 10.3% exclusively formula-fed. Although we found significant differences in BMI-for-age z-score (p = 0.033) and BMI-percentile-for-age (p = 0.023), there was no significant differences in fat mass and percent fat mass between the groups. Formula-fed children tended to have slightly higher fat-free mass and percent fat-free mass than both mix-fed and exclusively breastfed children although these differences were not statistically significant. Conclusions: Our findings suggest that the direction of the association between early infant feeding and childhood obesity may be dependent on the indicators used to assess obesity.